The Disparagement of Pain: Social Influences on Medical Thinking - Harold Merskey; Robert W Teasell (Pain Research and Management, 2000)
Patients with pain often feel that their suffering is taken lightly, dismissed or denied. Before the introduction of anesthesia, pain was regarded as an awful affliction. This view diminished somewhat once anesthesia became available, although it still holds true for some forms of pain, eg, pain associated with terminal cancer. Pain was then treated as less troublesome when it became a reason for disability compensation to be paid. Examples are given of the disparagement of complaints by individuals reporting pain in the past 150 years. Factors that encourage doctors to underestimate patients' pain include the requirement for doctors to control the issue of narcotics; circumstances in which patients may benefit from compensation by claiming that their pain is great; and the development of attitudes that understate the importance of the relief of pain and overstate the importance of activity, exercise and not complaining. Current attitudes in this respect are associated with the insurance industry, but it has been shown that, even patients who do not have a compensable injury or have pain that is not disabling fail to receive the treatment for pain that is appropriate, eg, postoperatively. The present paper reviews and discusses these problems and suggests that disparagement of pain and disability in the medicolegal field also leads to the rejection of pain in other contexts.